2020
DOI: 10.1016/j.ijso.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and factors associated with postoperative nausea and vomiting among elective adult surgical patients at University of Gondar comprehensive specialized hospital, Northwest Ethiopia, 2019: A cross-sectional study

Abstract: Background: Postoperative nausea and vomiting is a common complication of anaesthesia and surgery. It is considered the most common cause of morbidity following anaesthesia and has significant effects on patient satisfaction and cost. Despite modern anaesthetic and surgical techniques, the incidence of PONV remains high. Objective: The objective of this study was to determine the incidence of postoperative nausea and vomiting and associated factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
6
1
Order By: Relevance
“…It is postulated that a history of PONV points to the presence of an underlying susceptibility to PONV [ 6 ]. This finding was also in agreement with the findings of other studies that were conducted in Ethiopia [ 20 ], Korea [ 21 ] and Uganda [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is postulated that a history of PONV points to the presence of an underlying susceptibility to PONV [ 6 ]. This finding was also in agreement with the findings of other studies that were conducted in Ethiopia [ 20 ], Korea [ 21 ] and Uganda [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although non-smoking status and postoperative opioid use were among the predictors of PONV in Apfel’s predictive model [ 19 ], no such associations were significant in the current study, similar to other studies from Ethiopia [ 20 ] and Uganda [ 22 ]. Furthermore, a study that assessed PONV in patients undergoing arthroscopic surgery concluded that short-acting opioids did not have a significant effect on patients’ risk of developing PONV [ 32 ].…”
Section: Discussionsupporting
confidence: 84%
“…Although we cannot assign causality to this association, it is in agreement with previous studies linking duration of hospitalization to PONV. [10][11][12][13][14][15][16] This would be a particularly important benefit of PONV reduction, as hospital capacity is frequently a major challenge in low-income settings.…”
Section: Discussionmentioning
confidence: 99%
“…Unresolved PONV may result in a prolonged postanesthesia care unit (PACU) stay and unanticipated prolonged hospital admission, which results in a significant increase in overall health care cost. 9–16…”
mentioning
confidence: 99%
See 1 more Smart Citation